Challenges in simultaneous interpretation - Aimuratova, Nilufar Tengel kizi (Science and Education, 2023)
Simultaneous interpretation is a mode of interpreting in which the interpreter converts what the speaker says into the foreign language in actual time besides disrupting the authentic float of delivery. In other words, the interpreter has to interpret what the speaker says at the identical time as the speaker is announcing it. The duties performed by means of the simultaneous interpreter consist of performing a number of movements nearly simultaneously: listening to the source language, perception the content material of the speech, translating it into the target language and speaking back.